Proteinuria in Apparently Healthy Elderly Dogs: Persistency and Comparison Between Free Catch and Cystocentesis Urine. (25th December 2016) - Marynissen, S.J.J.; Willems, A.L.; Paepe, D.; Smets, P.M.Y.; Picavet, P.; Duchateau, L.; Daminet, S.
Abstract : Background: Up to 25% of elderly humans have proteinuria, often associated with underlying lesions. Data concerning the presence of proteinuria in elderly dogs is scarce. Objectives: To describe the presence and persistence of proteinuria and to compare urinary protein : creatinine ratio (UPC) between free catch and cystocentesis urine samples in apparently healthy elderly dogs. Animals: Hundred apparently healthy elderly dogs. Methods: Prospective study. Owners of 100 elderly dogs were asked to collect 2 free catch urine samples. Dogs were considered healthy based on owner's perception and an age chart, based on ideal bodyweight, was used to define dogs as senior or geriatric. UPC of urine collected by free catch and cystocentesis were compared. Overt proteinuria and borderline proteinuria were defined as UPC >0.5 and between 0.2 and 0.5, respectively, if examination of sediment did not explain proteinuria. Proteinuria was considered persistent if present at both sampling times. Results: At baseline, 71 owners succeeded in collecting urine. Eleven percent of dogs had overt proteinuria, 14% were borderline proteinuric, and 75% nonproteinuric. Thirty‐seven repeated urine samples, with a median time interval of 31 days (range 10–90), were available. Nineteen percent of dogs had a persistently increased UPC (>0.2), with persistent overt proteinuria present in 8%. A strong correlation (ρ = 0.88) was found between UPC of urine collected by free catch and cystocentesis. Conclusions and Clinical Importance: As 19% of study dogs had persistent proteinuria, our findings emphasize that measurement of proteinuria should be part of geriatric health screening. For UPC in dogs, free catch urine provides a good alternative to cystocentesis.